Application of pre-Terra Preta to enhance soil fertility and productivity of marginal land cultivated with Pennisetum purpureum cv. Mott - Dewi Priany Nasution; Udiansyah Udiansyah; Fakhrur Razie; Nursyam Andi Syarifuddin; Dora Neina (Universitas Sebelas Maret, 2025)
Indonesia’s national agriculture production is increasingly constrained by the expansion of marginal lands with low productivity, many of which have undergone severe degradation from mining and other land uses. These lands are characterized by low soil fertility and acidic pH, posing a challenge for sustainable forage production. This study investigates the application of pre-Terra Preta - a soil amendment composed of biochar, organic matter, animal manure, topsoil, and fermented microorganisms—to enhance the productivity of marginal land, using Pennisetum purpureum cv. Mott (Dwarf elephant grass) as a forage crop. The field experiment was conducted in Swarangan Village, Tanah Laut Regency, South Kalimantan, Indonesia. Soil chemical properties were analyzed before and after planting. A total of 36 plots (5 × 5 m) were treated with four levels of pre-Terra Preta biochar composition (0%, 20%, 40%, and 60%) and three application rates (10, 20, and 30 t ha⁻¹). The results showed significant improvements in soil chemical properties, including total N (↑ 73.47%), organic C (↑ 35.20%), K₂O (↑ 33.64%), and pH (↑ 148.89%). The optimal treatment—30 t ha⁻¹ with 60% biochar—yielded the highest plant height (16.875 cm), number of leaves (12.900), and number of tillers (3.791). These differences were significant (p < 0.05), confirming the effectiveness of both biochar levels and application rates. Pre-Terra Preta offers a sustainable, cost-effective strategy for rehabilitating marginal lands in tropical regions. Further studies are recommended to assess long-term soil health, economic viability, forage quality, and livestock performance.